A comparative review of German and South African environmental law with special reference to pollution control - Schulze, Ekkehard (Centre for Law and Society, 2024)
In this, dissertation the principles, instruments · and remedies of German and South African environmental law are examined, as far as they are relevant for pollution control. The purpose is to investigate whether the two countries can learn from each other. In the beginning three principles are discussed which have been formative on German environmental law. The principle of prevention which aims at minimising pollution regardless of its actual hazard and the polluter-pays principle are considered important for an effective environmental law. In general the so-called principle of co-operation appears to have no specific effectivity. Administrative law is then examined. While control the two there procedures are similar in are substantial differences as far pollutioncountries, as judicial control of administrative acts is concerned. In Germany permits for emitters can be challenged by anybody living in the vicinity of a polluting installation; German 2 administrative courts may always reconsider the merits of an administrative .decision. In South Africa concerned citizens may not contest the licence to operate an installation, unless their real or personal rights are infringed; even in the latter case the normally not consider the merits a decision. courts may In Germany environmental impact assessments and public participation are obligatory in many cases. While in South Africa their implementation is left to the discretion of the Minister of Environment Affairs and other ministers involved. The main difference between German and South African criminal law is that the penalties, in particular fines, are far lighter in South Africa. Environmental protection by means of private-law remedies differs considerably in the two countries. The injunction is a primary remedy in Germany which requires the infringement of real or personal rights of the plaintiff. The interdict under South African law is a subsidiary remedy only available where an action for damages does not afford adequate protection; yet the interdict can be based upon the infringement of rights of personality. 3 Under the new UmweltHG (Environmental Liability Act) strict liability and a presumption of causality has been introduced in Germany for major installations and activities. In South Africa the burden of proving a causal relationship is always upon the plaintiff; strict liability has only been implemented for nuclear installations. In Germany various emission fees and tax concessions are in force or under consideration. In South Africa no financial incentives have been introduced to date to promote emission control. Lastly environmental protection by a means of a human right or legislative objective is examined. The intention is to insert the objective into the German constitution that the environment is to be protected. A similar idea of including a legal principle of environmental protection into the Environment Conservation Act has been abandoned in South Africa. It is suggested that pollution fees should be introduced on all levels in order to minimise pollution. Such fees have in principle proved to be effective Tax law should be supplemented by an improved civil, administrative and criminal law. 4 In the field of civil law strict liability and a relaxation advisable. of the burden of proving Public participation procedures causality is should become mandatory in licensing procedures. should be increased considerably. Criminal penalties In Germany it is advisable to introduce the possibility for an injunction if rights of personality are infringed since environmental degradation does not cause violation of real or personal rights.